Association of Right Ventricular Infarction in Patients with Inferior Wall Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: Inferior wall myocardial infarction (MI) which presents hypotension is highly suggestive of associated Right ventricular (RV) Infarction leading to high mortality, therefore demand special precautions in its management. We conducted this study to see this potentially lethal combination of inferior wall MI withRVinfarction.Study Design: Descriptive cross sectional study.Place and Duration of Study: This study was conducted at the Department of Cardiology, Bahawalpur Victoria Hospital, Bahawalpur, during 23rd September 2015 to 22nd March 2016.Materials and Methods: This study was conducted at Department of Cardiology, Bahawalpur Victoria Hospital, Bahawalpur. It’s a descriptive, cross sectional study comprises of 87 patients who were diagnosed on admission as inferior wall myocardial infarction of age 30-60 years of either gender were included. Patients with anterior wall MI, Left bundle branch block, cor-pulmonale, pulmonary hypertension and renal failure were excluded.In all patients standard twelve ECG along with right sided chest leads was performed and evaluated for association of RV infarction.Results: Mean age was 52.55 ± 9.27 years. Number of male patients was 68 (78.16%) and females were 19 (21.84%) in the study with ratio of 3.6:1. Right ventricular infarction was found in 35 (40.23%) patients, whereas52 (59.77%) patients had no associated RV infarction.Conclusion: This study showed that inferior wall MI is significantly associated with RV infarction.